Does Financial Repression Facilitate Financial Development? Empirical Evidence from Malaysia - Zulham, Masitah; Abdullah, Dewi Fariha; Ridzuan, Abdul Rahim (International Journal of Economics and Financial Issues, 2025)
The importance of financial repression to the Malaysian financial development appears to be recognised. Lengthy theoretical and empirical discussions in previous literature have taken place on determinant of financial development which are focusing on macroeconomic factors. However, they ignore the role of financial repression as a determinant for financial development. Thus, the main purpose of this study is to examine the effect of financial repressions and their causality effects on financial development in Malaysia. There are five proxies used to measure financial repression which are public debt, statutory reserve requirement, liquidity requirement, interest rate control, and directed credit program. Other variable such as gross domestic product (GDP), inflation, human capital, and gross fixed capital formation also included as control variable. This study employed 42 years’ time series data for the period of 1980-2022. Augmented Dickey Fuller (ADF) unit root test and Phillip Perron unit root tests are applied to test the stationarity properties of the series. This study uses Principal Component Analysis (PCA) to measure financial repression index (FRI). Its address the problem of multicollinearity or high correlation between the various financial repression indicators. This study also employed the Autoregressive Distributed Lag (ARDL) Model to examine the long-run robustness and short-run dynamics of independent variables on Malaysia’s financial development. The causal relationship between the variables is further investigated using the Toda Yamamoto Granger non-causality test. Overall, the result shows, there is a negatively significant relationship between financial repression index and financial development. All variables LNFD, LNGDP, LNINF, LNHC and LNGFCF causes LNFRI. However, there is no bi-directional causality (feedback hypothesis) detected in this model. The government could avoid a major policy reversal to reinforce the gains of the reform program. Instead, the government should focus on fine-tuning current policy positions and implementing a stable macro-financial climate based on standard macroeconomic policies with a stable interest rate and lower inflation.